2022
DOI: 10.1021/acsearthspacechem.1c00400
|View full text |Cite
|
Sign up to set email alerts
|

Aeolian Dust and Sea Salt in Marine Aerosols over the Arabian Sea during the Southwest Monsoon: Sources and Spatial Variability

Abstract: The nutrient supply to the oceanic surface water is largely regulated by the extrinsic and intrinsic ambient atmospheric aerosol properties, particularly chemistry. In this context, we measured the comprehensive chemical composition (inorganic ions and major elements) of atmospheric aerosols and studied their spatial distribution over the Arabian Sea during the southwest monsoon (SWM) period for 2 consecutive years (2017 and 2018). We found that the water-soluble ionic concentration (WSIC) is dominated by Na+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…A 10 mL aliquot of extracted leachate was acidified for water-soluble TE analyses, and another aliquot was stored in a deep freezer (−20 °C) till its analysis for cations and anions. Details of analyses of cation and anion using ion chromatography can be found in Aswini et al…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A 10 mL aliquot of extracted leachate was acidified for water-soluble TE analyses, and another aliquot was stored in a deep freezer (−20 °C) till its analysis for cations and anions. Details of analyses of cation and anion using ion chromatography can be found in Aswini et al…”
Section: Methodsmentioning
confidence: 99%
“…This region experiences a seasonal reversal of wind due to the monsoon system; thus, the calculated annual DF will have large uncertainty. Considering this, we have estimated the seasonal average DF using V d = 1 cm s –1 for crustal elements (Fe and Mn) associated with coarser dust; however, for Cu, we used V d = 0.3 m s –1 , considering its association with a finer anthropogenic fraction. , In previous studies, Srinivas and Sarin, as well as Pryor and Sørensen, have reported that an increase in wind speed can increase the sub-micron size particle, which is prevalant in the ARS during monsoon months as compared to other seasons …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…8,[34][35][36] In addition, efforts have been made to measure the chemical composition of aerosols under the aegis of several national and international programs in India. 13,14,19,23,25,32,[37][38][39][40] Combining several snapshot measurements, Srinivas and Sarin 38 estimated that dry deposition of inorganic nutrients supports $13% of the surface primary production in the Bay of Bengal (BoB) and $5% of the surface primary production in the Arabian Sea (AS) during the dry period. Similarly, Yadav et al 32 highlighted that $70% of the total suspended particulate matter (TSP) was deposited within 10 km from the coast and can support 3 to 33% of the coastal surface primary production during fall and winter seasons in the BoB.…”
Section: Introductionmentioning
confidence: 99%